Characterization of pulp derived nanocellulose hydrogels using AVAP® technology. (15th October 2018) - Kyle, Stuart; Jessop, Zita M.; Al-Sabah, Ayesha; Hawkins, Karl; Lewis, Aled; Maffeis, Thierry; Charbonneau, Cecile; Gazze, Andrea; Francis, Lewis W.; Iakovlev, Mikhail; Nelson, Kim; Eichhorn, Stephen J.; et al.
Highlights: NC fibrils, CNCs and a novel blend were prepared from softwood biomass using the AVAP® biorefinery technology. NC formulations were extensively characterized using an array of techniques. This study assessed nano- and microarchitecture, surface topography, porosity, thermal properties and rheology. NC hydrogels show enormous potential in (bio)nanomaterial applications. Abstract: Bioinspiration from hierarchical structures found in natural environments has heralded a new age of advanced functional materials. Nanocellulose has received significant attention due to the demand for high-performance materials with tailored mechanical, physical and biological properties. In this study, nanocellulose fibrils, nanocrystals and a novel mixture of fibrils and nanocrystals (blend) were prepared from softwood biomass using the AVAP® biorefinery technology. These materials were characterized using transmission and scanning electron microscopy, and atomic force microscopy. This analysis revealed a nano- and microarchitecture with extensive porosity. Notable differences included the nanocrystals exhibiting a compact packing of nanorods with reduced porosity. The NC blend exhibited porous fibrillar networks with interconnecting compact nanorods. Fourier transform infrared spectroscopy and X-ray diffraction confirmed a pure cellulose I structure. Thermal studies highlighted the excellent stability of all three NC materials with the nanocrystals having the highest decomposition temperature. Surface charge analysis revealed stable colloid suspensions. Rheological studies highlighted a dominance of elasticity in all variants, with the NC blend being more rigid than the NC fibrils and nanocrystals, indicating a double network hydrogel structure. Given these properties, it is thought that these materials show great potential in (bio)nanomaterial applications where careful control of microarchitecture, surface topography and porosity are required.